2012
DOI: 10.1063/1.3697710
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved monitoring of cavitation activity in megasonic cleaning systems

Abstract: The occurrence of acoustic cavitation in the cleaning liquid is a crucial precondition for the performance of megasonic cleaning systems. Hence, a fundamental understanding of the impact of different parameters of the megasonic process on cavitation activity is necessary. A setup capable of synchronously measuring sonoluminescence and acoustic emission originating from acoustically active bubbles is presented. The system also includes a high-speed-stroboscopic Schlieren imaging system to directly visualize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 28 publications
1
35
1
Order By: Relevance
“…PRE tests have been carried out at those optimal conditions, chosen on the basis of the previously reported hydrophone measurements, and are presented in Table I. Hauptmann 17 recently reported that under continuous sonication and at low acoustic power densities the obtained particle removal efficiency is limited. Cavitation activity can be enhanced when pulsing the acoustic field, as shown in Sec.…”
Section: Pre and Damage Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRE tests have been carried out at those optimal conditions, chosen on the basis of the previously reported hydrophone measurements, and are presented in Table I. Hauptmann 17 recently reported that under continuous sonication and at low acoustic power densities the obtained particle removal efficiency is limited. Cavitation activity can be enhanced when pulsing the acoustic field, as shown in Sec.…”
Section: Pre and Damage Testsmentioning
confidence: 99%
“…A more detailed description and illustration of the experimental setup can be found elsewhere. 17 Once the acoustic spectrum is recorded and averaged, the ultraharmonics (from 2.5 to 5.5 times the resonant frequency) are evaluated. Different types of cavitation are often 114322-2distinguished when evaluating acoustic noise spectra.…”
Section: B Test Apparatus For Acoustic Cavitation Studymentioning
confidence: 99%
“…The hydrophone signal was amplified using a homemade amplifier based on the AD8066 FastFET operational amplifier (Analog Devices) (Hauptmann et al 2012).…”
Section: Pcd-based Cavitation Noise Methodsmentioning
confidence: 99%
“…The data were fourier transformed to obtain the fundamental frequency of acoustic fields and the amplitude of the 2nd, 3rd and 4th harmonic acoustic pressure. The amplitude of fundamental frequency was set as the standard to normalize the data, where the normalized data represented the acoustic cavitation according to the method of Hauptmann et al (17). The experiments were repeated four times.…”
Section: Western Blot Analysis B-cell Lymphoma 2 (Bcl-2) Andmentioning
confidence: 99%
“…The acoustic cavitations were detected according to the method of Hauptmann et al (17). Hydrophones were placed into tubes which were filled with A7r5 cells treated with ultrasound (US group) or ultrasound combined with microbubbles (US+MB group), and the change of acoustic fields was detected over time.…”
Section: Western Blot Analysis B-cell Lymphoma 2 (Bcl-2) Andmentioning
confidence: 99%